2020
DOI: 10.1002/jbm.b.34753
|View full text |Cite
|
Sign up to set email alerts
|

The use of solvents for gutta‐percha dissolution/removal during endodontic retreatments: A scoping review

Abstract: This scoping review study aimed to map the evidence about solvents' use for gutta‐percha dissolution and removal during endodontic retreatments. The study protocol followed the Joanna Briggs Institute guidelines, available online (https://osf.io/5vy8n/). Reporting was based on PRISMA Extension for Scoping Reviews. We selected dentistry studies that considered the effectiveness of solvents in gutta‐percha dissolution in endodontic retreatments and compared their performance to the use of instrumentation techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 44 publications
0
17
0
2
Order By: Relevance
“…[ 20 ] Nonetheless, clinicians should be cautious with the use of solvents such as chloroform due to its toxicity and carcinogenic potential. [ 59 60 61 62 ] Furthermore, the use of solvents would create a thin layer of plasticized gutta-percha adhering to the root canal wall and its irregularities making the operatory time longer and retreatment procedure challenging. [ 63 64 ] Garrib and Camilleri[ 65 ] reported that a chemical adjunct (10% formic acid) along with mechanical instrumentation is efficient to retreat teeth obturated with gutta-percha and bioceramic sealer as it eliminated over 95% of root canal filling material as well as re-established apical patency and working length.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 ] Nonetheless, clinicians should be cautious with the use of solvents such as chloroform due to its toxicity and carcinogenic potential. [ 59 60 61 62 ] Furthermore, the use of solvents would create a thin layer of plasticized gutta-percha adhering to the root canal wall and its irregularities making the operatory time longer and retreatment procedure challenging. [ 63 64 ] Garrib and Camilleri[ 65 ] reported that a chemical adjunct (10% formic acid) along with mechanical instrumentation is efficient to retreat teeth obturated with gutta-percha and bioceramic sealer as it eliminated over 95% of root canal filling material as well as re-established apical patency and working length.…”
Section: Discussionmentioning
confidence: 99%
“…Effective gutta-percha solvents include e.g. chloroform or eucalyptol (Dotto et al, 2021). It does not adhere to the dentin of the root system and, therefore, all filling techniques using gutta-percha cones require their combination with sealer material.…”
Section: Obturation Of Root Canals -Equipment and Materialsmentioning
confidence: 99%
“…Many scientists failed to convert EUR into elastomer for a long time. 18,19 Therefore, to realize the transformation of EUR from plastic to elastic, it is the key to break through the barrier of the crystallization of EUR. Until 1980s, EUR elastomer was first fabricated using vulcanization technology by Yan, thus ending the history that EUR cannot be used as elastic rubber.…”
Section: Introductionmentioning
confidence: 99%
“…EUR is a crystalline polymer and serves as hard rubber with strong impact resistance performance at the ambient temperature, while NR needs low temperature (−25 °C) or stretch to induce the crystallization. Many scientists failed to convert EUR into elastomer for a long time. , Therefore, to realize the transformation of EUR from plastic to elastic, it is the key to break through the barrier of the crystallization of EUR. Until 1980s, EUR elastomer was first fabricated using vulcanization technology by Yan, thus ending the history that EUR cannot be used as elastic rubber .…”
Section: Introductionmentioning
confidence: 99%